Designing and developing IoT based security system for smart home. (3rd October 2022) - Sharifuzzaman, Md.; Islam, Jahidul; Chowdhury, Suman
Abstract: This paper represents Internet of Things (IoT) based security system for smart home. As technology has progressed and the use of IoT has grown, digital door locks have become increasingly common. Door Security System application uses ESP8266 and IoT technology to monitor the status of the door. Blynk is a communication protocol that allows a smartphone to communicate with a door lock system. The Door Security System is available on Android and iOS. With this automation system, users may utilize an IR (Infrared remote) remote to manage their home security system from afar. We attempted to connect door security system in our home. Obviously, we will be able to solve that problem in the future. WiFi modules connect to our home internet router and link to our IoT server. Our Android and Web applications communicate with the server as well. This program allows users to check the current state of their home appliances and control them from anywhere. Also MQ3 indicates higher overall performance than the MQ2 in phrases of distance and reaction time.